Hydroxyurea pharmacokinetics and precision dosing in low-resource settings - Smart, Luke R.; Charles, Mwesige; McElhinney, Kathryn E.; Dong, Min; Power-Hays, Alexandra; Howard, Thad; Vinks, Alexander A.; Ambrose, Emmanuela E.; Ware, Russell E. (Frontiers in Molecular Biosciences, 2023)
Introduction: Hydroxyurea is effective disease-modifying treatment for sickle cell anemia (SCA). Escalation to maximum tolerated dose (MTD) achieves superior benefits without additional toxicities, but requires dose adjustments with serial monitoring. Pharmacokinetic (PK)-guided dosing can predict a personalized optimal dose, which approximates MTD and requires fewer clinical visits, laboratory assessments, and dose adjustments. However, PK-guided dosing requires complex analytical techniques unavailable in low-resource settings. Simplified hydroxyurea PK analysis could optimize dosing and increase access to treatment. Methods: Concentrated stock solutions of reagents for chemical detection of serum hydroxyurea using HPLC were prepared and stored at -80C. On the day of analysis, hydroxyurea was serially diluted in human serum, then spiked with N-methylurea as an internal standard and analyzed using two commercial HPLC machines: (1) standard benchtop Agilent with 449nm detector and 5 micron C18 column; and (2) portable PolyLC SmartLife with 415nm detector and 3.5 micron C18 column. After validation in the United States, the portable HPLC and chemicals were transported to Tanzania. Results: A calibration curve using hydroxyurea 2-fold dilutions ranging from 0-1000µM was plotted against the hydroxyurea:N-methylurea ratio. In the United States, both HPLC systems yielded calibration curves with R2 >0.99. Hydroxyurea prepared at known concentrations confirmed accuracy and precision within 10-20% of the actual values. Both HPLC systems measured hydroxyurea with <10% variance from the prepared concentrations, and paired analysis of samples on both machines documented <15% variance. Serial measurements of 300 and 100 μM concentrations using the PolyLC system were precise with 2.5% coefficient of variance. After transport to Tanzania with setup and training, the modified SmartLife HPLC system produced similar calibration curves with R2 >0.99. Conclusions: Increasing access to hydroxyurea for people with SCA requires an approach that eases financial and logistical barriers while optimizing safety and benefits, especially in low-resource settings. We successfully modified a portable HPLC instrument to quantify hydroxyurea, validated its precision and accuracy, and confirmed capacity building and knowledge transfer to Tanzania. HPLC measurement of serum hydroxyurea is now feasible in low-resource settings using available laboratory infrastructure. PK-guided dosing of hydroxyurea will be tested prospectively to achieve optimal treatment responses.